Numerical analysis of Ni/Al hybrid metal foams using the finite cell method. Issue 1 (21st October 2015) - Heinze, Stephan; Chen, Zhaoyu; Jung, Anne; Diebels, Stefan; Düster, Alexander
Abstract: Aluminium metal foams are a new type of material that can be used in many lightweight applications. One method to improve their mechanical properties is to coat them with a thin layer of nickel by electrodeposition. A voxel representation of this hybrid foam can be obtained in a straightforward way using a CT scanner. The voxel‐based geometry can then be processed and modified with respect to the thickness of the nickel layer in order to investigate its influence on the effective properties. By employing the finite cell method (FCM) we are able to automatically convert the voxel‐based geometry into a finite cell grid and to directly perform a homogenization procedure. (© 2015 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)